Molecular variation of the nonribosomal peptide‐polyketide siderophore yersiniabactin through biosynthetic and metabolic engineering. Issue 5 (20th November 2015) - Ahmadi, Mahmoud Kamal; Fawaz, Samar; Fang, Lei; Yu, Zhipeng; Pfeifer, Blaine A
ABSTRACT: The production of the mixed nonribosomal peptide‐polyketide natural product yersiniabactin (Ybt) has been established using E. coli as a heterologous host. In this study, precursor‐directed biosynthesis was used to generate five new analogs of Ybt, demonstrating the flexibility of the heterologous system and the biosynthetic process in allowing compound diversity. A combination of biosynthetic and cellular engineering was then used to influence the production metrics of the resulting analogs. First, the cellular levels and activity of FadL, a hydrocarbon transport protein, were tested for subsequent influence upon exogenous precursor uptake and Ybt analog production with a positive correlation observed between FadL over‐production and analog formation. Next, a Ybt biosynthetic editing enzyme was removed from the heterologous system which decreased native compound production but increased analog formation. A final series of experiments enhanced endogenous anthranilate towards complete pathway formation of the associated analog which showed a selective ability to bind gold. Biotechnol. Bioeng. 2016;113: 1067–1074. © 2015 Wiley Periodicals, Inc. Abstract : Precursor‐directed biosynthesis was used to generate five new analogs of the yersiniabactin (Ybt) compound from a heterologous E. coli production platform. Preferential gold binding was observed for an anthranilate analog compound compared to native Ybt. The approach and engineering strategies provided in this study serve as a basis in future work to be directed at applications such as metal retrieval and re‐use across industrial and environmental engineering settings.